2019
DOI: 10.3390/ma12183043
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of SMA490BW Steel and Welded Joints for High-Speed Trains in Atmospheric Environments

Abstract: Currently, high-speed trains work under various atmospheric environments, and the bogie as a key component suffers serious corrosion. To investigate the corrosion behavior of bogies in industrial atmospheric environments, the periodic immersion wet/dry cyclic corrosion test for SMA490BW steel and automatic metal active gas (MAG) welded joints used for bogies was conducted in the present work. Corrosion weight loss rate, structure, and composition of rust layers as well as electrochemistry parameters were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This can block the penetration of the corrosive medium and slow the weathering of the steel, thereby reducing its corrosion rate. Therefore, when the weathering steel is in an industrial environment, the corrosion rate is as shown in figure 3(b), and the corrosion rate increases during the early stage, and the corrosion rate decreases during the later stage [35].…”
Section: Corrosion Dynamicsmentioning
confidence: 99%
“…This can block the penetration of the corrosive medium and slow the weathering of the steel, thereby reducing its corrosion rate. Therefore, when the weathering steel is in an industrial environment, the corrosion rate is as shown in figure 3(b), and the corrosion rate increases during the early stage, and the corrosion rate decreases during the later stage [35].…”
Section: Corrosion Dynamicsmentioning
confidence: 99%
“…Simultaneously, the grain refinement and work-hardening effects after ultrasonic treatment led to an increase in surface microhardness. Wu et al [7] studied the corrosion behavior of SMA490BW used for high-speed train bogies and its welded joints using a periodic wet/dry cycle corrosion test simulating an industrial atmospheric environment. The results show that the corrosion weight loss rate decreased with an increase in the corrosion time.…”
Section: Introductionmentioning
confidence: 99%
“…However, aluminum alloy structures may be damaged due to wear or corrosion when they are in service in harsh and complex environments. For example, the car bodies of high-speed trains made from aluminum alloys may suffer from corrosion and aging in complex atmospheric environments [1][2][3]. In addition, the car bodies may be partially injured under the impact of external forces, such as scratches, pits, and laceration.…”
Section: Introductionmentioning
confidence: 99%